Reflexiones acerca de la hegemonía de la ciudad sobre el campo en América Latina - Gómez, Carlos Norberto C. (2021)
Fil: Fil: Gómez, Carlos Norberto C. Universidad Nacional de la Patagonia San Juan Bosco (UNPSJB).Universidad Nacional de la Patagonia Austral (Pcia. de Santa Cruz); Argentina